2018
DOI: 10.1039/c8nr05159c
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir–Blodgett self-assembly of ultrathin graphene quantum dot films with modulated optical properties

Abstract: Macro-scale assembly of graphene quantum dots has great potential in diverse applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…As one of the chalcogens (group-VI materials), tellurium (Te) is well known as a p-type semiconductor with a bandgap of 0.35 eV at room temperature and possesses a wealth of intriguing properties [1] such as photoconductivity [2], thermoelectricity [3], and piezoelectricity [4]. Since atomically thin graphene flakes were discovered in 2004 [5,6], two-dimensional (2D) materials have triggered intensive research interest for the fabrication of nanodevices on an industrial scale [7][8][9][10][11][12][13][14][15]. However, the development of 2D materials faces significant challenges, such as the zero bandgap of graphene [16,17], the environmental instability of black phosphorus (BP) [18][19][20][21][22], the low current mobility of transition metal dichalcogenides (TMDCs) [23], and the lack of large-scale and efficient synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the chalcogens (group-VI materials), tellurium (Te) is well known as a p-type semiconductor with a bandgap of 0.35 eV at room temperature and possesses a wealth of intriguing properties [1] such as photoconductivity [2], thermoelectricity [3], and piezoelectricity [4]. Since atomically thin graphene flakes were discovered in 2004 [5,6], two-dimensional (2D) materials have triggered intensive research interest for the fabrication of nanodevices on an industrial scale [7][8][9][10][11][12][13][14][15]. However, the development of 2D materials faces significant challenges, such as the zero bandgap of graphene [16,17], the environmental instability of black phosphorus (BP) [18][19][20][21][22], the low current mobility of transition metal dichalcogenides (TMDCs) [23], and the lack of large-scale and efficient synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…The Fe2p in Figure 2g illustrated the presence of Fe 3 O 4 . The XPS spectra further demonstrated that there were Fe 3 O 4 , PPy and GQDs in the nanocomposites [3,21,25]. Studies have shown that excellent fluorescent luminescence performance is one of the most outstanding properties of graphene quantum dots [11,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al used a LB technique to fabricate ultrathin, high-quality GQD aggregated films with well-modulated optical properties in a wide range of wavelengths. 225 Through the combination of a bottom-up synthesis of GQDs and the LB assembly method, uniform, closely packed, and ultra-thin GQD films can be self-assembled with a well-controlled thickness on different substrates. Stanković et al prepared by LB technique uniform and homogeneous CQDs thin films.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%